2020
DOI: 10.1002/btpr.3102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variable domain orientation on anti‐HER2 single‐chain variable fragment antibody expressed in the Escherichia coli cytoplasm

Abstract: Single-chain variable fragment (scFv) antibodies have great potential for a range of applications including as diagnostic and therapeutic agents. However, production of scFvs is challenging because proper folding and activity depend on the formation of two intrachain disulfide bonds that do not readily form in the cytoplasm of living cells. Functional expression in bacteria therefore involves targeting to the more oxidizing periplasm, but yields in this compartment can be limiting due to secretion bottlenecks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…3c ). Nearly identical results were obtained when CFGpS reactions were primed with plasmid DNA encoding a different acceptor POI, namely an scFv antibody specific for human epidermal growth factor receptor 2 (scFv-HER2) that was modified at its C-terminus with a DQNAT glycosylation tag 14,43 ( Fig. 3b and c ).…”
Section: Resultsmentioning
confidence: 61%
“…3c ). Nearly identical results were obtained when CFGpS reactions were primed with plasmid DNA encoding a different acceptor POI, namely an scFv antibody specific for human epidermal growth factor receptor 2 (scFv-HER2) that was modified at its C-terminus with a DQNAT glycosylation tag 14,43 ( Fig. 3b and c ).…”
Section: Resultsmentioning
confidence: 61%
“…Importantly, the mRNA encoding SecM17-stalled Im7 N58 was stably attached to ribosomes, as evidenced by the prominent amplicon generated via RT-PCR of ribosome-associated RNA (Figure 3c). Nearly identical results were obtained when CFGpS reactions were primed with plasmid DNA encoding a different POI, namely, an scFv antibody specific for human epidermal growth factor receptor 2 (scFv-HER2) that was modified at its C-terminus with a DQNAT glycosylation tag 6,24 (Figure 3b,c). Using immobilized HER2 as the antigen, we selected glycoRNC complexes displaying glycosylated scFv-HER2 DQNAT −SecM17 and observed that the encoding mRNA remained associated with these functionally selected glycoRNCs (Figure 3d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Expression of soluble antibody proteins is the first required step for determining antibody protein quality and functional activity. In fact, a large number of studies have been focused on improving expression of soluble and stable scFv antibodies using various bacterial and yeast expression systems [ 20 , 39 41 ]. Among existing expression systems, those based on E. coli have become popular for use in scFvs preparation, although use of an E. coli -based system to generate the two intrachain disulfide bonds necessary for antibody folding and antigen-binding activity can be challenging [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a large number of studies have been focused on improving expression of soluble and stable scFv antibodies using various bacterial and yeast expression systems [ 20 , 39 41 ]. Among existing expression systems, those based on E. coli have become popular for use in scFvs preparation, although use of an E. coli -based system to generate the two intrachain disulfide bonds necessary for antibody folding and antigen-binding activity can be challenging [ 20 ]. To address this problem, researchers have designed various strategies to produce functional scFvs by promoting their accumulation within the periplasm, where the oxidising environment supports disulfide bond formation and corrects scFv folding [ 20 , 37 , 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation